Oboczność ir // er (≤ *ŕ̥) w Księgach o gospodarstwie (Kraków 1549, Helena Unglerowa) - Osiewicz, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
This article is a continuation of research into the textual differentiation of the distribution of the variant phonetic forms in Księgi o gospodarstwie by Piotr Krescentyn of 1549. The analysis includes forms with the ir // er (≤ *ŕ̥) groups. While the diversity of the textual distribution of the surveyed forms pertains to only six roots: -ḿ_řv-, -v́_řb-, -ṕ_rv-, -č_rń, -tv́_rʒ-, -v́_řx-, it is quite considerable as it encompasses 10 textual areas coinciding with the text segmentation typical of previous (graphic and phonetic) analyses. Three text layers indicate the typesetter’s intervention. As for the analysed form, the part containing the 381a–R10v quarts was the most standardised chunk of the text; it is also quite conservative with respect to the solutions in the area analysed. The analysis also demonstrates that the demarcation line between the Q and R quarts, as indicated by Kazimierz Piekarski on the basis of a typographic analysis, coincides with the demarcation line of phonetic phenomena.